HUBUNGAN JENIS PESTISIDA DENGAN FUNGSI HEPAR PETANI DI DESA SIKAPAT KECAMATAN SUMBANG KABUPATEN BANYUMAS - Laksana, Agung Saprasetya Dwi; Aminudin, Fikri; Fadlilah, Synta Haqqul (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Farming activities were one of the main occupations in Banyumas Regency. Pesticides were often used to exterminate pests that harmed agricultural yields, but their improper use could adversely affect body organs, including the liver. This research aimed to determine the relationship between types of pesticides based on their usage function and liver function in farmers in Sikapat Village, Sumbang District, Banyumas Regency. This study was an observational analytic study with a cross-sectional design. The study population consisted of farmers using pesticides in Sikapat Village, Sumbang District, Banyumas Regency, from March to October 2023. Farmers who were willing to participate in the study and were present during data collection were included as research subjects. The sample was taken using the purposive sampling method. Liver function was measured by examining AST and ALT levels, while pesticide use data were obtained using a questionnaire. Data analysis used the Chi-square test with Fisher's or Kolmogorov-Smirnov alternatives at a significance level of 0.05. Results showed that there was an increase in ALT and AST was only observed in the group of farmers using a combination of pesticides (p=0.259). The highest average ALT levels were reported in the use of combined pesticides (26.2 ± 12.9 U/L), followed by insecticides (21.4 ± 2.5 U/L), herbicides (19.4 ± 5.2 U/L), and fungicides (15.1 ± 1.1 U/L) (p=0.072). The highest average AST levels were reported in the use of combined pesticides (24.2 ± 5.3 U/L), followed by fungicides (21.8 ± 1.2 U/L), insecticides (21.7 ± 3.9 U/L), and herbicides (20.8 ± 2.6 U/L) (p=0.157). In conclusion, there was no relationship between the use of pesticide types and liver function in farmers in Sikapat Village, Sumbang District, Banyumas Regency.